2001
DOI: 10.1103/physrevlett.86.4996
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Frequency Measurements of theHg+and Ca Optical Clock Transitions with a Femtosecond Laser

Abstract: The frequency comb created by a femtosecond mode-locked laser and a microstructured fiber is used to phase coherently measure the frequencies of both the Hg + and Ca optical standards with respect to the SI second as realized at NIST. We find the transition frequencies to be fHg = 1 064 721 609 899 143(10) Hz and fCa = 455 986 240 494 158(26) Hz, respectively. In addition to the unprecedented precision demonstrated here, this work is the precursor to all-optical atomic clocks based on the Hg + and Ca standards… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
80
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 235 publications
(81 citation statements)
references
References 25 publications
0
80
0
1
Order By: Relevance
“…In fact there is a large shift of the g factor of the 3 P 0 state compared to that of the 1 S 0 state that has recently been measured. 37 It was found that g( 3 P 0 ) = -0.001 976 86(21) and g( 1 S 0 ) = -0.000 792 48 (14), where the g factors are defined in terms of the Bohr magneton, and the numbers in parentheses are the uncertainties in units of the least significant digits. The shift of g( 3 P 0 ) relative to g( 1 S 0 ) is due to the hyperfine interaction mixing the 3 P 0 with other other J states, mainly 3s3p 3 P 1 .…”
Section: Atomic Systemmentioning
confidence: 99%
“…In fact there is a large shift of the g factor of the 3 P 0 state compared to that of the 1 S 0 state that has recently been measured. 37 It was found that g( 3 P 0 ) = -0.001 976 86(21) and g( 1 S 0 ) = -0.000 792 48 (14), where the g factors are defined in terms of the Bohr magneton, and the numbers in parentheses are the uncertainties in units of the least significant digits. The shift of g( 3 P 0 ) relative to g( 1 S 0 ) is due to the hyperfine interaction mixing the 3 P 0 with other other J states, mainly 3s3p 3 P 1 .…”
Section: Atomic Systemmentioning
confidence: 99%
“…In neutral atom systems, the Dick limit is usually well above fundamental limits such as quantum projection noise [6] and often corresponds closely with experimentally observed clock instability (e.g. [1,7,8]). Improving LO stability directly reduces the Dick effect both by reducing the frequency noise that is aliased and by enabling longer atomic probing, which reduces the fractional 'dead' time between consecutive probe cycles.…”
mentioning
confidence: 99%
“…This makes them strong candidates for reaching measurement instability ≤ 10 −17 in 1 s. However, this stability remains far from realized. In a seminal research effort in 2001, two optical atomic clocks at NIST were directly compared with a frequency comb [1]. The instability of these clocks was shown to be at record levels, ∼ 4 × 10 −15 / √ τ (for measurement time τ ).…”
mentioning
confidence: 99%
“…In some specially designed resonators it is nowadays possible to generate octave-spanning spectra that support pulses shorter than 5 fs (Ell et al, 2001), and these ultra-broadband pulses are used to synthesize optical combs (Holzwarth et al, 2000;Ye & Cundiff, 2005). These optical combs are frequency synthesizers with uncertainties bellow 10 -15 that are being used as time standards replacing atomic clocks (Takamoto et al, 2005), and to absolutely measure optical frequencies (Reichert et al, 1999;Udem et al, 2001). These combs are also used to stabilize the phase between the pulse carrier frequency and its envelope to a few milirads, corresponding to tens of attoseconds (Telle et al, 1999).…”
Section: Ultrashort Pulses Nonlinear Opticsmentioning
confidence: 99%